Elevated Expression of TLR2 in Aging Hearts Exacerbates Cardiac Inflammatory Response and Adverse Remodeling Following Ischemia and Reperfusion Injury - Zhai, Yufeng; Ao, Lihua; Yao, Qingzhou; The, Erlinda; Fullerton, David A.; Meng, Xianzhong (Frontiers in Immunology, 2022)
This study tested the hypothesis that Toll-like receptor 2 (TLR2) augments the inflammatory responses and adverse remodeling in aging hearts to exacerbate myocardial injury and cardiac dysfunction. Methods Old (20-22 months old) and adult (4-6 months old) mice of C57BL/6 wild-type and TLR2 knockout (KO) were subjected to coronary artery ligation (30 minutes) and reperfusion (3 or 14 days). Left ventricle function was assessed using a pressure-volume microcatheter. Cardiac infarct size was determined by histology. Levels of vascular cell adhesion molecule-1 (VCAM-1), intercellular adhesion molecule-1 (ICAM-1), matrix metalloproteinase 9 (MMP 9), and collagen I in non-ischemic myocardium were assessed by immunoblotting. Monocyte chemoattractant protein-1 (MCP-1), keratinocyte chemoattractant (KC), and interleukin-6 (IL-6) levels in ischemic and non-ischemic myocardium were measured by enzyme-linked immunosorbent assay (ELISA). TLR2 expression in the myocardium of untreated wild type mice was also measured by immunoblotting. Results Higher levels of MCP-1, KC, IL-6 were induced in both ischemic and non-ischemic myocardium of old wild type mice at day 3 and 14 following ischemia/reperfusion (I/R) than those of adult wild type mice. The hyper-inflammatory responses to I/R in aging hearts were associated with elevated levels of myocardial TLR2. TLR2 KO markedly down-regulated the expression of MCP-1, KC, IL-6, ICAM-1 and VCAM-1 in aging hearts at day 3 and 14 following I/R. The down-regulated inflammatory activity in aging TLR2 KO hearts was associated with attenuated production of MMP 9 and collagen I at day 14 and resulted in reduced infarct size and improved cardiac function. Conclusion Elevated expression of myocardial TLR2 contributes to the mechanism by which aging exacerbates the inflammatory responses, adverse remodeling and cardiac dysfunction following myocardial I/R in aging.